A new multi analytical approach for the identification of synthetic and natural dyes mixtures. The case of orcein-mauveine mixture in a historical dress of a Sicilian noblewoman of nineteenth century. Issue 7 (3rd April 2019) - Serafini, Ilaria; Lombardi, Livia; Fasolato, Claudia; Sergi, Manuel; Di Ottavio, Francesca; Sciubba, Fabio; Montesano, Camilla; Guiso, Marcella; Costanza, Rita; Nucci, Lucia; Curini, Roberta; Postorino, Paolo; et al.
Abstract: In this paper, the application of a multi-analytical approach for the characterisation of synthetic and natural dyes in a historical textile is presented. The work is focused on a historical dress of a Sicilian noblewoman, dating from about 1865–1870. Firstly, SERS on fibre was performed, in order to individuate the classes of dyes employed. The SERS spectra suggested the presence of two main dyes: mauveine and orcein. In order to confirm these preliminary results, two different extraction protocols were applied. The extracts obtained were analysed by ESI-MS, MALDI-ToF and UHPCL-MS analyses, confirming the SERS results. In particular, the application of the ammonia mild extraction technique allowed to selectively extract the phenoxazonic dyes, separating them already in the extraction step from the synthetic ones. Thanks to this multi-analytical approach, this dress could be considered as one of the first examples of employment of synthetic dyes in association with natural ones. Abstract :